2020
DOI: 10.1093/nar/gkaa854
|View full text |Cite
|
Sign up to set email alerts
|

Understanding DNA interactions in crowded environments with a coarse-grained model

Abstract: Nucleic acid interactions under crowded environments are of great importance for biological processes and nanotechnology. However, the kinetics and thermodynamics of nucleic acid interactions in a crowded environment remain poorly understood. We use a coarse-grained model of DNA to study the kinetics and thermodynamics of DNA duplex and hairpin formation in crowded environments. We find that crowders can increase the melting temperature of both an 8-mer DNA duplex and a hairpin with a stem of 6-nt depending on… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 59 publications
0
24
0
Order By: Relevance
“…The first hypothesis is that macromolecular crowding effects, such as a depletion force, are stronger in the Dex/PEG twophase systems than in the dextran single-phase system and favor DNA aggregation. The depletion force is a force with an entropic origin often seen in macromolecular crowding environments that manifest in polymer solutions, favoring the self-assembly of biopolymers (Marenduzzo et al, 2006), and which can stabilize the DNA duplex (Nakano et al, 2004;Hong et al, 2020). The assembly of DNA tile microtubes (Zhang et al, 2020) and compacting genomic DNA (Zhang et al, 2009) under macromolecular crowding conditions have also been reported.…”
Section: Discussionmentioning
confidence: 99%
“…The first hypothesis is that macromolecular crowding effects, such as a depletion force, are stronger in the Dex/PEG twophase systems than in the dextran single-phase system and favor DNA aggregation. The depletion force is a force with an entropic origin often seen in macromolecular crowding environments that manifest in polymer solutions, favoring the self-assembly of biopolymers (Marenduzzo et al, 2006), and which can stabilize the DNA duplex (Nakano et al, 2004;Hong et al, 2020). The assembly of DNA tile microtubes (Zhang et al, 2020) and compacting genomic DNA (Zhang et al, 2009) under macromolecular crowding conditions have also been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, thermodynamic studies have shown that crowded systems can stabilize DNA duplexes and hairpin formation through pure entropy sources. The use of a relatively crowded environment can increase the strand replacement rate [10]. The low melting point agarose is in a dynamic process of solid-liquid change at 30°C and is capable of existing in the MDA system as a macromolecule like PEG.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that polymers such as PEG are capable of improving the efficiency of PCR amplification, and molecular crowding effect of PEG might be the main reason [9,10]. Agarose, the most commonly used experimental material in molecular biology, in its solidified state can form a porous structure.…”
Section: Introductionmentioning
confidence: 99%
“…In the treatment of the effects of macromolecular crowding, we assume that all chemical species are homogeneously distributed or well-mixed and, thus, consider only the time evolution of the concentrations or particle numbers of reactants and products. In the presence of molecular crowders, the rate constants of reaction steps may be affected, and the degree of influence varies widely among the different types of reaction steps involved.…”
Section: Macromolecular Crowdingmentioning
confidence: 99%
“…At the cellular level, besides the reaction being contained in a small volume, the environments of proteins are crowded with other biomolecules, such as DNA, lipids, other proteins, etc. The fraction of volume occupied by these “crowders” can be as high as 30–40%, which can affect the reaction rates of proteins as well as other biopolymers in the cell in significant ways. …”
Section: Introductionmentioning
confidence: 99%